Ürojinekolojide ve Kadın İnkontinansında Güncel Perspektif - Gürel, Duygu; Kol, Arif; Körkoca, Ayfer; İpek, Osman Murat and Malak, Arzu and Keten, Tanju and Doğrusever, Mehmet Burak and Dayısoylu, Hulusi Sıtkı and Şahin, Mehmet Fatih and Özcan, Rıdvan and Tok, Doğan Sabri and Akyol, Safa and Sevinç, Ahmet Halil and Şambel, Murat and Kılıç, Şahin and Hancı Sevinç, Burcu and Çakmak, Sedat and Dinçer, Erdinç and Gülaç, Bekir and Arıkan, Mehmet Gürkan and Üstün, Fatih and Özgüç, Semiha and Temel, Mustafa Hüseyin and Özcan İşler, Seda and Şeramet, Serkan and Halisçelik, Mesut Ali and Kayaalp, Hüseyin and Andıç, Esra (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-